2018
DOI: 10.1017/s1474747218000082
|View full text |Cite
|
Sign up to set email alerts
|

An experimental analysis of modifications to the survivor benefit information within the Social Security statement

Abstract: The Social Security Statement is the primary resource most workers prefer to use to learn about their Social Security benefits. The Social Security Administration periodically mails this and supporting documents to all workers to help them make informed decisions about when to start receiving their benefits. Understandably, the Statement provides detailed information about the worker's retirement benefit. However, these documents contain remarkably little information about the survivor benefit despite the fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 28 publications
3
11
1
Order By: Relevance
“…The Social Security Statement is a natural outlet for communications about benefit design because past studies have shown that it succeeds at improving knowledge, although it seems to have little effect on actual behavior (Biggs 2010;Mastrobuoni 2011;Smith and Couch 2014). Consistent with these earlier studies, Diebold and Camilleri (2018) find that information about benefit design increases planned claiming ages by about one year, but that the effect disappears in a follow-up survey three months later. The treatment effect could dissipate because respondents -married men ages 30 to 61 -are too far away from retirement to seriously contemplate widowhood.…”
Section: Literature Reviewsupporting
confidence: 84%
See 4 more Smart Citations
“…The Social Security Statement is a natural outlet for communications about benefit design because past studies have shown that it succeeds at improving knowledge, although it seems to have little effect on actual behavior (Biggs 2010;Mastrobuoni 2011;Smith and Couch 2014). Consistent with these earlier studies, Diebold and Camilleri (2018) find that information about benefit design increases planned claiming ages by about one year, but that the effect disappears in a follow-up survey three months later. The treatment effect could dissipate because respondents -married men ages 30 to 61 -are too far away from retirement to seriously contemplate widowhood.…”
Section: Literature Reviewsupporting
confidence: 84%
“…A lack of knowledge about survivor benefits could contribute to the decision to claim early. A number of surveys report high rates of ignorance about key features of Social Security survivor benefits, including the fact that a husband's actuarial penalty for claiming early carries over to his widow's survivor benefit (Brown and Perron 2011;Greenwald et al 2010;Liebman and Luttmer 2012;and Diebold and Camilleri 2018). Similarly, Sass et al (2007) cautiously interpret the positive relationship between educational attainment and claiming age as evidence that husbands with higher financial literacy improve the well-being of their widows.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations